THE LESER–TRÉLAT SIGN AS A PARANEOPLASTIC MANIFESTATION OF MALIGNANCY: A REVIEW OF THE LITERATURE - Milović, Jelena (Srpski medicinski časopis Lekarske komore, 2026)
Introduction/Objective: The Leser–Trélat sign is a paraneoplastic dermatosis characterized by the sudden, eruptive appearance and rapid increase in number and size of multiple seborrheic keratoses, often accompanied by intense pruritus. This clinical presentation may raise suspicion of an underlying malignancy. Although its exact pathophysiological mechanism remains unclear, tumor-derived growth factors are believed to stimulate keratinocyte proliferation, contributing to the abrupt development of lesions. In the literature, the Leser–Trélat sign is most frequently associated with gastrointestinal adenocarcinomas, particularly gastric carcinoma, but it has also been reported in connection with other solid tumors and hematologic malignancies. Given its potential association with occult neoplasm, the appearance of the Leser–Trélat sign warrants a thorough clinical evaluation and systematic diagnostic workup, as timely recognition may facilitate early detection of the underlying malignancy. The aim of the paper is to analyze data from the available literature on the etiology, pathogenesis, and clinical associations of the Leser–Trélat sign with various malignancies, and to evaluate its diagnostic and prognostic significance in contemporary clinical practice. Methods: A literature review was conducted using the PubMed database, including available original articles, review papers, case reports, and case series. The search was performed using the following keywords: “Leser–Trélat sign”, “paraneoplastic dermatosis”, “seborrheic keratoses”, and “malignancy”. Conclusion: Awareness of the Leser–Trélat sign and a multidisciplinary approach to investigating its association with malignancies are crucial for the early detection of neoplasms. Recognition of the Leser–Trélat sign may enable the diagnosis of malignancy at a stage when therapeutic response is more favorable, thereby significantly improving disease prognosis.